2018
DOI: 10.1002/pra2.2018.14505501063
|View full text |Cite
|
Sign up to set email alerts
|

Empowering communities with data: Role of data intermediaries for communities' data utilization

Abstract: Data have significant potential to address current societal problems not only at the federal and state levels, but also in smaller communities, in neighborhoods, and in the lives of individuals. While the proposition for this potential is that data are and will be shared with and reused by and for communities at different levels, not all data are systematically or routinely shared for reuse with communities due to social, structural and technical infrastructure barriers. Data intermediary organizations can pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…Even if they were part of a community data collection and representation, they were often seen as a passive player and, thus, excluded from local data collection design; instead, they rather passively participated in a given setting, without a chance to ask questions or raise their voices to reflect their opinions. The tensions and controversies generated by this passive participation from the top‐down approach in community engagement are not new (e.g., Stuedahl, Runardotter, & Mörtberg, 2016; Yoon et al, 2018) and made the communities question the openness and deemed desire and trust in open data context.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Even if they were part of a community data collection and representation, they were often seen as a passive player and, thus, excluded from local data collection design; instead, they rather passively participated in a given setting, without a chance to ask questions or raise their voices to reflect their opinions. The tensions and controversies generated by this passive participation from the top‐down approach in community engagement are not new (e.g., Stuedahl, Runardotter, & Mörtberg, 2016; Yoon et al, 2018) and made the communities question the openness and deemed desire and trust in open data context.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps this is why many community organizations face needs and shortcomings in their own data collections. Previous studies have also reported that community organizations, with or without partnership with academic or data intermediary organizations, collect local data to complement these limitations in existing data sets, but not all are equipped with the proper financial or human resource capacities (Yoon et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The degree to which local (municipal or state) OGD users differ from national OGD users is not fully explored. While a study of OGD users of Raleigh Open Data suggests that local users largely fit the profile of those who work in the tech industry (O'Conner, , p. 28), interviewees in another study reported that “‘a lot of people (from the community) were intimidated’ when using secondary data” and that “publicly available raw data are often not user‐friendly to community members” (Yoon, Copeland, & McNally, , pp. 4–5).…”
Section: Literature Reviewmentioning
confidence: 99%